RESEARCH ON WINTER WHEAT, CORN AND SUNFLOWER CROPS PROTECTION IN ILFOV COUNTY RESPECTING NATIONAL LEGISLATION - Steluța LIPIANU; Cristinel Relu ZALĂ; Rada ISTRATE; Costică CIONTU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Plant health (in this case winter wheat, corn and sunflower crops) is fundamental to the sustainability and competitiveness of agriculture, food safety and environmental protection. Currently, modern winter wheat, corn and sunflower crop protection strategies are focused on combating harmful organisms (diseases, weeds and pests) that cause quantitative and qualitative losses to these crops. The research in this paper focused on the presentation of all plant protection products applied to wheat, corn and sunflower crops by 50 farmers from Ilfov county in the 2019 agricultural year. The assortment of fungicides, insecticides and herbicides used is extremely varied. We also made observations in the field to identify which diseases and pests were present in the crops and consulted the farmers on the extent of their control. The degree of attack of powdery mildew, two weeks after the application of the treatments, was calculated based on the incidence and severity of the diseases. The diagnosis of diseases was made by visual observation of the typical symptoms of their manifestations. Information from farmers was obtained on the basis of questionnaires. Total control of weeds in farmers' crops was provided by an assortment represented by 8 wheat herbicides, 2 sunflower herbicides and 10 maize herbicides. Due to environmental concerns and concern for human health, the application of products for the protection of wheat, corn and sunflower crops was done taking into account good practices in the context of promoting integrated management of diseases, weeds and pests according to European directive 2009/128/EC.